Design of a Low Sidelobe Feed Network Based on the Louver-Shaped Defected Ground Structure - Yuan Zhang; Songtao Xi (International Journal of Antennas and Propagation)
In this paper, a low sidelobe feeding network has been developed utilizing the louver-shaped defected ground structure (DGS). By adjusting the louver-shaped DGS, the output amplitude and phase of the corresponding ports can be altered, minimizing deviations from theoretical values. This enables antenna arrays equipped with this feeding network to more easily achieve low sidelobe performance. The impact of the louver-shaped DGS on the amplitude and phase of each port in the power divider within the feeding network is analyzed, and a 16-channel feeding network incorporating the louver-shaped DGS has been designed, fabricated, and then measured. The test results indicate that the performance of the line-feeding network is effectively improved by designing and adjusting the louver-shaped DGS. Through the debugging procedure, the amplitude deviation of the feeding network has been reduced from ±0.45 dB to ±0.2 dB, while the phase deviation of the feeding network has been reduced from ±8° to ±2.5°, and the maximum value of the first sidelobe has been reduced from −24.2 dB to −28.1 dB.